2010
DOI: 10.5551/jat.4234
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of C-Reactive Protein to High-Molecular-Weight Adiponectin Ratio to Predict Insulin Resistance and Metabolic Syndrome in Japanese Men

Abstract: Aim:We questioned whether the ratio of C-reactive protein to high-molecular-weight adiponectin (C/A ratio), compared to each value alone, is more useful to predict insulin resistance and/or metabolic syndrome. Methods: We measured serum CRP and HMW adiponectin levels in 841 Japanese men who had participated in an annual health checkup. Correlations of the C/A ratio with metabolic parameters were assessed, and its predictive values for insulin resistance and MetS were compared with CRP or HMW adiponectin alone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Several studies have demonstrated that many people with MetS have an elevated hsCRP concentration [5], which may predict their risk for future adverse events [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that many people with MetS have an elevated hsCRP concentration [5], which may predict their risk for future adverse events [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin and CRP are independent risk factors of CVD, together serve a synergistic role in metabolic regulation in the general population and T2D subjects [35][36][37] . We found that AA women with high adiponectin and low CRP levels, which translated into a high ratio, had significantly lower FG, IN, HOMA-IR, WC, %BF and BMI relative to those with a low ratio.…”
Section: Comparedmentioning
confidence: 99%
“…High serum hsCRP levels are seen in MetS and studies demonstrated that increased serum hsCRP level is an important inflammatory marker in the risk of cardiovascular disease (26)(27)(28)(29). In the CU pathogenesis, increased serum CRP level was reported and it showed positive correlation with disease activity (5,17,30).…”
Section: Discussionmentioning
confidence: 99%